Effects of high-intensity training on jumping performance among athletes: a systematic review with meta-analysis - Xinzhi, Wang; Kim, Geok Soh; Samsudin, Shamsulariffin; Li, Long; Liu, Chunqing; Sun, Min; Ma, Shuzhen (Nature Research, 2025)
This review aims to conduct a meta-analysis of the impact of high-intensity training (HIT) on athlete jumping performance. As of May 2024, we conducted a comprehensive search on PubMed, Web of Science, SCOPUS, and EBSCOhost databases in accordance with the PRISMA guidelines. Use the PEDro scale to evaluate the methodological quality of the included study. Meta-analysis of random effects model calculations. Conduct subgroup analysis (participant age, gender, training experience, intervention length and frequency). 18 high-quality studies met the inclusion criteria, including 490 athletes aged between 6 and 27 years old. The results showed that high-intensity interval training (HIIT) has a moderate effect on athlete jumping performance (ES = 0.918), while high-intensity functional training (HIFT) has a small effect on athlete jumping performance (ES = 0.581). The sub analysis of moderating variables includes 19 datasets. Compared with the control group, HIT has a positive impact on the jumping performance of athletes. The training experience, age, gender, intervention frequency, and intervention length of participants did not have a significant impact on the jumping performance of athletes, indicating the applicability of HIT as a training method. However, more extensive exercise experiments are needed to obtain stronger evidence.